Effects of butyl toluidine blue photosensitizer on antimicrobial photodynamic therapy for experimental periodontitis treatment in rats - Nuernberg, Marta Aparecida Alberton [UNESP]; Wainwright, Mark; Miessi, Daniela Maria Janjacomo [UNESP]; Scalet, Vitor [UNESP]; Olivo, Mariane Bocalon [UNESP]; Ervolino, Edilson [UNESP]; Garcia, Valdir Gouveia [UNESP]; Theodoro, Letícia Helena [UNESP] (Elsevier, 2020)
Aim: This study evaluated three concentrations of butyl toluidine blue (BuTB) for antimicrobial photodynamic therapy (aPDT) in experimental periodontitis (EP) in rats. Material and methods: EP was ligature-induced at the first mandibular molar in 105 rats. Ligature was removed after 7 days and animals were distributed into the following treatments: SRP, scaling and root planing (SRP) plus saline solution; BuTB-0.1, SRP plus BuTB at 0.1 mg/mL; aPDT-0.1, SRP plus BuTB at 0.1 mg/mL and InGaAlP diode laser (DL) irradiation; BuTB-0.5, SRP plus BuTB at 0.5 mg/mL; aPDT-0.5, SRP plus BuTB at 0.5 mg/mL and DL irradiation; BuTB-2.0, SRP plus BuTB at 2 mg/mL; aPDT-2.0, SRP plus BuTB at 2 mg/mL and DL irradiation. Five animals from each group were submitted to euthanasia at 7, 15 and 30 days post-treatment. The furcation area was submitted to histological, histometric and immunohistochemical (TGF-ß1, OCN and TRAP) analyses. Results: aPDT-0.5 group presented a better tissue remodeling in all periods, resolution of the inflammatory response and bone neoformation areas at 30 days. aPDT-0.5 also resulted in higher immunolabeling patterns of TGF-ß1 at all periods (p < 0.05) and of OCN at 30 days (p < 0.05). Conclusion: aPDT-0.5 showed the best benefits for inflammatory response and periodontal repair process.
Keywords: Animal disease model; Dental scaling; Periodontitis; Photochemotherapy; Photosensitizers